The Impact of Public Debt on Economic Growth and Revenue Generation in Nepal: An Analysis from 1974/75 to Present - Binod Joshi,; Gyan Mani Adhikari, (Nepalese Journal of Management Research, 2025)
The complex relationship between public debt, economic growth, and revenue generation is an essential aspect of macroeconomic management, particularly for developing nations like Nepal. This paper offers an in-depth analysis of Nepal’s foreign and domestic debt management practices from 1974/75 to the present, focusing on the evolution of public debt and its interplay with economic growth, revenue generation, and fiscal sustainability. The period around 1974/75 marked a significant turning point for Nepal, initiating a shift in the country’s reliance on external financing due to domestic fiscal constraints and political instability. Through an extensive review of historical data, economic theories, and comparative analysis with other South Asian nations, this paper explores how both internal and external debt have affected Nepal’s development trajectory, revenue systems, and long-term growth prospects. Using a variety of economic models and principles, including debt-overhang, Ricardian equivalence, and the fiscal multiplier, the study provides a comprehensive understanding of how public debt influences national economic outcomes. The paper further investigates the challenges associated with debt sustainability, rising debt servicing costs, and the crucial role of domestic revenue generation in managing Nepal’s debt trajectory. With robust empirical data from credible sources, this study provides a thorough examination of Nepal’s debt history, policy reforms, and economic outcomes. It offers new insights into the importance of managing both external and internal debt effectively to ensure long-term fiscal health and sustainable growth. The paper concludes with policy recommendations on debt management, revenue mobilization, and growth strategies for Nepal and other countries facing similar challenges.